Associations between exercise classes and self-reported exercise by people with Parkinson's disease at Parkinson's foundation centers of excellence. (2022) - Nettnin, Ella; Burrows, Stephanie; Miao, Guanhong; Wu, Samuel S.; Simon, David K.; Rafferty, Miriam R.; ,
Abstract: Introduction: Despite evidence of the benefits of exercise, people with Parkinson's disease (PD) often exercise less than recommended. We sought to identify exercise class-related factors associated with the amount of exercise in PD communities. Methods: We used Parkinson's Outcome Project (POP) data from 3146 people with PD at 19 participating Centers of Excellence (COEs). POP data included self-reported moderate-vigorous exercise (MVE) hours, light physical activity (PA) hours, demographic and disease severity variables. We also collected information about weekly exercise class availability, intensity, cost, and distance from class location to the COE. We examined differences between COE-based and community-based exercise classes using the Akritas test for paired and unpaired samples. We tested associations between class characteristics and exercise hours based on a two-part model: logistic regression on whether a participant does MVE or light PA and linear regression for log-transformed time of exercise. Results: Community-based exercise classes had a significantly higher weekly availability than COE-based classes (class hours per week: 47.5 ± 25.6 vs 6.5 ± 8.6, p < 0.001), a higher percentage of vigorous-intensity classes (24.2 ± 17.8 vs 11 ± 14.7, p < 0.001), and a broader geographic distribution (miles to COE: 12.8 ± 4.6 vs 6.2 ± 5.7, p < 0.001). Greater weekly hours of availability, intensity, and distance to COE were associated with increased MVE and light PA hours among participants who exercised (p < 0.01). Of these, higher weekly class availability explained the most variability in reported exercise hours. Conclusion: Parkinson's COEs may be able to increase exercise by facilitating a high weekly availability of exercise classes with higher intensity levels and broader geographical distribution.